The greatest showman [videorecording (Blu-Ray + DVD)] - Bicks, Jenny; Condon, Bill, 1955-; Jackman, Hugh; Williams, Michelle, 1980-; Efron, Zac; Ferguson, Rebecca, 1983-; Zendaya, 1996-; Settle, Keala, 1975-; McGarvey, Seamus, 1967-; Pasek, Benj; Pasek, Benj; Paul, Justin, 1985-; et al. (Twentieth Century Fox Home Entertainment, 2018)
A musical dramatization of the life story of P.T. Barnum -- the creator of the Barnum & Bailey Circus.